2012
DOI: 10.1007/s11434-012-5279-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical method for mapping QTLs for complex traits based on two backcross populations

Abstract: Most important agronomic and quality traits of crops are quantitative in nature. The genetic variations in such traits are usually controlled by sets of genes called quantitative trait loci (QTLs), and the interactions between QTLs and the environment. It is crucial to understand the genetic architecture of complex traits to design efficient strategies for plant breeding. In the present study, a new experimental design and the corresponding statistical method are presented for QTL mapping. The proposed mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Zhihong et al ( 2012 ) have also highlighted the advantages of this design, also known as the double backcross design and is used for constituting an immortal mapping population, allowing for across-environment replications, estimation of dominance effects, epistatic effects, and QTL-environment interactions, and thus remedies the drawbacks of a single backcross population. Recent studies on QTL mapping in rice, maize, cotton, and B. napus have shown that dominance and epistasis, especially the additive × additive interaction, play a key role in contributing to heterosis (Stuber et al, 1992 ; Yu et al, 1997 ; Tang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhihong et al ( 2012 ) have also highlighted the advantages of this design, also known as the double backcross design and is used for constituting an immortal mapping population, allowing for across-environment replications, estimation of dominance effects, epistatic effects, and QTL-environment interactions, and thus remedies the drawbacks of a single backcross population. Recent studies on QTL mapping in rice, maize, cotton, and B. napus have shown that dominance and epistasis, especially the additive × additive interaction, play a key role in contributing to heterosis (Stuber et al, 1992 ; Yu et al, 1997 ; Tang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first article [1] is a review of statistical approaches for QTL mapping and marker-assisted breeding that were developed by the authors and their group. In subsequent articles, several new QTL mapping methods are proposed for specific experimental designs, including (1) the use of two backcross populations [2], (2) the use of a NCIII design based on recombinant inbred lines [3], and (3) the use of chromosome segment substitution lines [4]; or for specific purposes, namely, (1) to detect epistasis between nuclear genes (QTLs) and the cytoplasm [5], and (2) to map sterile genes (QTLs) with epistasis in remote hybridization of plant [6]. In another article [7], an improved approach for QTL mapping in farm animals based on general pedigrees, termed pedigree transmission disequilibrium test, is proposed; this method performs better than existing statistical methods.…”
mentioning
confidence: 99%
“…A similar design was earlier adopted by Radoev et al (2008) and Basunanda et al (2010) for studying heterosis for seedling biomass and yield traits. Zhihong et al (2012) have also highlighted the advantages of this design, also known as the double backcross design and is used for constituting an immortal mapping population, allowing for across-environment replications, estimation of dominance effects, epistatic effects, and QTL-environment interactions, and thus remedies the drawbacks of a single backcross population. Recent studies on QTL mapping in rice, maize, cotton, and B. napus have shown that dominance and epistasis, especially the additive × additive interaction, play a key role in contributing to heterosis (Stuber et al, 1992;Yu et al, 1997;Tang et al, 2010).…”
Section: Advantages Of the Experimental Design For Genetic Analysis Of Heterosismentioning
confidence: 99%